Assessment of Nitrogen Oxide Emissions and San Joaquin Valley PM2.5 Impacts From Soils in California. Issue 24 (17th December 2020) - Guo, Lei; Chen, Jianjun; Luo, Dongmin; Liu, Shang; Lee, Hyung Joo; Motallebi, Nehzat; Fong, Angel; Deng, Jia; Rasool, Quazi Z.; Avise, Jeremy C.; Kuwayama, Toshihiro; Croes, Bart E.; et al.
Abstract: Soils are a source of atmospheric nitrogen oxides (NOx ), especially in regions with significant cropland where nitrogen (N) fertilizers are used to enhance crop yields. The magnitude of soil NOx emissions, however, varies substantially by region, depending on the local land use pattern and management activities. We estimated soil NOx emissions in California based on the DeNitrification‐DeComposition (DNDC) biogeochemical model, linked to a detailed spatial‐temporal differentiated California‐specific database. The DNDC‐generated surface fluxes were used in the Community Multiscale Air Quality (CMAQ) model to evaluate impacts of soil NOx emissions on formation of ambient particulate (PM2.5 ) nitrate in the San Joaquin Valley (SJV) where cropland is the dominant land use. The DNDC‐generated soil NOx emissions contribute approximately 1.1% of total anthropogenic NOx emissions in California, at an emission rate of roughly 24 t day −1 (as NO2 ) statewide and 9 t day −1 in the SJV. Cropland is the dominant source of soil NOx emissions in California, contributing nearly 60% of statewide soil NOx emissions, driven principally by fertilizer use. The PM2.5 nitrate concentrations simulated by CMAQ using the DNDC‐generated soil NOx emissions are compatible with those observed in the SJV, suggesting that soil NOx emissions have limited impacts on PM2.5 nitrate formation in the atmosphere. Our emission and air quality modeling results are further supported by long‐term ambient NOx ‐to‐carbon monoxide (CO) and satellite NO2 data analyses in the SJV, which showed diurnal, monthly, and annual trends consistent with characteristics of NOx sources dominated by traffic combustion in both urban and agricultural regions. Plain Language Summary: Nitrogen oxides (NOx ) are air pollutants that can react with other chemicals in the air to form fine particulate matter and ozone, both of which pose adverse impacts to human health and the environment. Control of NOx emissions is critical to improving air quality in California. Soils are a known NOx source, especially in agricultural areas where large amounts of nitrogen fertilizers are used to increase crop yields. The nitrogen chemicals in soil can be converted into various nitrogen gases, including NOx, by soil microorganisms. The contribution of soil emissions to the total NOx budget varies by region, depending on land uses and management activities. This study modeled soil NOx emissions from different land covers in California and evaluated impacts of soil NOx emissions on the formation of ambient particulate nitrate in the San Joaquin Valley (SJV), where cropland is the dominant land use. Our results indicate that soil NOx is a relatively minor fraction of the total NOx budget in California and has a minor effect on atmospheric concentrations of particulate nitrate in the SJV. Ambient and satellite data analyses show traffic combustions being the dominate source of NOx emissions in both urban and agricultural areas of the SJV. Key Points: Soil NOx is a relatively minor fraction of the total NOx emissions in California, driven primarily by nitrogen fertilizer use in cropland Impact of soil NOx emissions on ambient PM2.5 nitrate formation is limited in the San Joaquin Valley of California Ambient and satellite data analyses show vehicular emissions dominating NOx emissions in both urban and agricultural areas of California